2001
DOI: 10.1002/ijc.10127
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of fatty acid synthase is an early and common event in the development of prostate cancer

Abstract: The expression of fatty acid synthase (FAS), a key lipogenic enzyme and potential target for antineoplastic therapy, was analyzed in 87 frozen needle biopsies of prostate cancer using a highly sensitive immunohistochemical detection technique (Envision). In comparison to normal or benign, hyperplastic glandular structures, which were all negative for FAS staining, immunohistochemical signal was evident in 24/25 low grade prostatic epithelial neoplasia (PIN) lesions, in 26/26 high grade PIN lesions and in 82/87… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
226
1
11

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(246 citation statements)
references
References 18 publications
8
226
1
11
Order By: Relevance
“…Fatty acid synthase mRNA and protein upregulation is one of the earliest and most common events in the development of prostate carcinoma, and a strong association between FASN and tumour initiation has been shown (Swinnen et al, 2002;Rossi et al, 2003). Accordingly, we found FASN expression to be much stronger in tumours than in BPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty acid synthase mRNA and protein upregulation is one of the earliest and most common events in the development of prostate carcinoma, and a strong association between FASN and tumour initiation has been shown (Swinnen et al, 2002;Rossi et al, 2003). Accordingly, we found FASN expression to be much stronger in tumours than in BPH.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid synthase immunostaining was homogeneously dispersed throughout the cytoplasm as described before (Swinnen et al, 2002;Rossi et al, 2003). Subcellular staining of MYC was predominantly cytoplasmic: in BPH, perinuclear focal granular immunostaining was observed on the luminal site of the cells, whereas malignant secretory cells showed a diffuse cytoplasmic immunostaining.…”
Section: Subcellular Expression Pattern Of Candidate Proteinsmentioning
confidence: 99%
“…Although enzymes of mitochondrial β-oxidation are not increased in prostate cancer [140], it has been shown that etomoxir-mediated inhibition of mitochondrial β-oxidation at the level of carnitine palmitoyltransferase 1 induces cell death in prostate cancer cell lines [143]. Interestingly, prostate cancer also induces fatty acid biosynthesis by overexpressing fatty acid synthase early during tumor progression without lipid accumulation [144,145], which is further consistent with 11 C-acetate PET/CT experiments [146]. Why a futile cycle of simultaneous fatty acid oxidation and fatty acid synthesis is beneficial to prostate cancer cells remains an open question.…”
Section: Early Stage Prostate Cancer Metabolismmentioning
confidence: 99%
“…Thus, FAS expression is generally low to undetectable in normal human tissues, other than the liver and adipose tissue. In contrast, FAS is overexpressed in many human tumours, including carcinoma of the breast (Milgraum et al, 1997;Wang et al, 2001b), prostate (Epstein et al, 1995;Swinnen et al, 2002), colon (Rashid et al, 1997), ovary (Gansler et al, 1997), endometrium (Pizer et al, 1998b), mesothelium (Gabrielson et al, 2001), lung (Piyathilake et al, 2000), thyroid (Vlad et al, 1999), and stomach (Kusakabe et al, 2002). Abnormally active endogenous fatty acid metabolism appears to be important for cancer cell proliferation and survival (Ookhtens et al, 1984).…”
mentioning
confidence: 99%
“…Abnormally active endogenous fatty acid metabolism appears to be important for cancer cell proliferation and survival (Ookhtens et al, 1984). Moreover, overexpression of FAS in breast, prostate, and thyroid cancers has been associated with more aggressive malignancies (Epstein et al, 1995;Gansler et al, 1997;Vlad et al, 1999;Swinnen et al, 2002). The preferential expression of FAS in cancer cells suggests that FAS could be a promising target for antitumour therapy (Kuhajda, 2006).…”
mentioning
confidence: 99%